Process and Product in ISLA Research: Courage, Commitment, and Tolerance for Ambiguity. Issue 1 (20th February 2022) - Ranta, Leila
Abstract: Stern (1983) reminds us of the ethical reasons for doing second language (L2) research. That is, given the considerable human and financial investments that go into language education, the practical activities of teaching "should not exclusively rely on tradition, opinion, or trial‐and‐error but should be able to draw on rational enquiry, systematic investigation, and, if possible, controlled experiment" (p. 57). Elsewhere Stern argues for the use of interdisciplinary teams to carry out such research. The studies in this special issue illustrate the aptness of Stern's advice. These articles present findings from a large‐scale classroom research project that compared a deductive approach to teaching Spanish grammar to guided induction using the PACE model. The multidisciplinary team made use of different types of data, which were examined through different theoretical lenses. This discussion article considers the implications of these studies for L2 research, educational practice, teacher education, and the relationship between theory and practice. Abstract :